2020
DOI: 10.1590/1518-8345.3081.3335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a breastfeeding educational intervention: a randomized controlled trial

Abstract: Objective: to assess the effect of a breastfeeding educational intervention on the counseling provided to postpartum women. Method: this is a randomized controlled trial including 104 postpartum women (intervention group = 52 and control group = 52) from a private hospital, whose educational intervention was based on the pragmatic theory and on the use of a soft-hard technology called Breastfeeding Educational Kit (Kit Educativo para Aleitamento Materno, KEAM). Women were followed-up for up to 60 days after c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
1
10
0
5
Order By: Relevance
“…Fica cada vez mais evidente a importância do suporte dado pelos profissionais de saúde para o apoio e promoção do AM e o prolongamento do tempo da amamentação. Dessa forma há necessidade da implementação de ações educativas voltadas para a mulher, reforçando as orientações sobre essa temática bem como no manejo de dificuldades que possam acontecer (Souza et al, 2020).…”
Section: Discussionunclassified
“…Fica cada vez mais evidente a importância do suporte dado pelos profissionais de saúde para o apoio e promoção do AM e o prolongamento do tempo da amamentação. Dessa forma há necessidade da implementação de ações educativas voltadas para a mulher, reforçando as orientações sobre essa temática bem como no manejo de dificuldades que possam acontecer (Souza et al, 2020).…”
Section: Discussionunclassified
“…El uso del modelo que se presenta en este estudio es una acción educativa novedosa que, dadas sus características de diseño, se diferencia de otros modelos enfocados hacia la promoción de la LM, tal como se puede apreciar en los artículos «Development and evaluation of a high-fidelity lactation simulation model for health professional breastfeeding education» (Sadovnikova et al, 2020) y «Efecto de una intervención educativa sobre lactancia materna: un ensayo clínico aleatorizado» (Souza et al, 2020). Así mismo, el modelo está enfocado hacia el aprendizaje sobre el funcionamiento de la glándula mamaria que, a largo plazo, busca que la población y la sociedad avancen en el reconocimiento de los beneficios que genera la LM, el establecimiento de una práctica exclusiva hasta los 6 meses de edad y complementaria hasta los dos años y más.…”
Section: R Esultadosunclassified
“…Furthermore, the nursing protocol needs to be tested related to studying what interventions could be beneficial in the context of breastfeeding, particularly in vulnerable populations. To support this, it has been shown that, when nurses carry out educational interventions aimed at mothers during their postpartum stay, not only does the rate of exclusively breastfeeding increase but, also, the risk of mood alterations is reduced [81].…”
Section: Limitations and Futures Perspectivesmentioning
confidence: 99%